Myocardial abscess – case report of a survivor of a fatal disease - Dr. Doddaiah Narayanappa; Dr. Hassan Sreenivasamurthy Rajani; Dr. Sunil Kumar S; Dr. Anil Kumar M.G.; Dr. Chandrashekhar C. (Pediatric Review: International Journal of Pediatric Research, 2019)
Myocardial abscess is a rare and usually a fatal complication which is often secondary to infective endocarditis but it is relatively a rare manifestation of staphylococcal septicemia especially in pediatric population. Here we are presenting a case of intramural myocardial abscess following right thigh abscessand septicemia caused by MRSA in an immunocompetent child with no structural heart disease. Incision and drainage of thigh abscess with aggressive appropriate antibiotic therapy saved the child despite the fatal myocardial abscess. Even in the absence of Infective endocarditis in staphylococcal septicemia, it is mandatory to look for myocardial abscess for early diagnosis and betteroutcome. A high index of clinical suspicion is required to make a prompt diagnosis.